Immediate effects of interoceptive awareness training through Mindful Awareness in Body-oriented Therapy (MABT) for women in substance use disorder treatment. Issue 1 (2nd January 2019) - Price, Cynthia J.; Thompson, Elaine A.; Crowell, Sheila E.; Pike, Kenneth; Cheng, Sunny C.; Parent, Sara; Hooven, Carole
Abstract: Background: Sensory information gained through interoceptive awareness may play an important role in affective behavior and successful inhibition of drug use. This study examined the immediate pre-post effects of the mind-body intervention Mindful Awareness in Body-oriented Therapy (MABT) as an adjunct to women's substance use disorder (SUD) treatment. MABT teaches interoceptive awareness skills to promote self-care and emotion regulation. Methods: Women in intensive outpatient treatment (IOP) for chemical dependency ( N  = 217) at 3 community clinics in the Pacific Northwest of the United States were recruited and randomly assigned to one of 3 study conditions: MABT + treatment as usual (TAU), women's health education (WHE) +TAU (active control condition), and TAU only. At baseline and 3 months post-intervention, assessments were made of interoceptive awareness skills and mindfulness, emotion regulation (self-report and psychophysiological measures), symptomatic distress (depression and trauma-related symptoms), and substance use (days abstinent) and craving. Changes in outcomes across time were assessed using multilevel mixed-effects linear regression. Results: Findings based on an intent-to-treat approach demonstrated significant improvements in interoceptive awareness and mindfulness skills, emotion dysregulation (self-report and psychophysiology), and days abstinent for women who received MABT compared with the other study groups. Additional analyses based on participants who completed the major components of MABT (at least 75% of the intervention sessions) revealed these same improvements as well as reductions in depressive symptoms and substance craving. Conclusions: Findings that interoceptive training is associated with health outcomes for women in SUD treatment are consistent with emerging neurocognitive models that link interoception to emotion regulation and to related health outcomes, providing knowledge critical to supporting and improving SUD treatment.